Pewarnaan Simpul Dengan Algoritma Welch-Powell Pada Traffic Light Di Yogyakarta - Ana Mardiatus Soimah; Noor Saif Muhammad Mussafi (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2013)
Traffic congestion is a problem which is often found in big cities in Indonesia. This requires a range of solutions, one of them with the settings of the traffic light. Traffic light arrangement can be completed with graph theory. Part of graph theory a graph coloring is used. Staining graf three i.e. coloring is differentiated into a knot, staining the sides, and staining region. This research examines the arrangements about traffic light using colorization algorithm Welch knot with Powell. The intersection of Data represented in the graph, which is then solved by coloring the vertices, then look for the value of the effective duration of the time compared to a traffic light settings occur at several intersections in Yogyakarta. Completion of traffic light arrangement using staining nodes provide alternative solutions duration lit the red light and green light is more effective than the secondary data at several intersections in Yogyakarta.